Pregnancy complications in COVID-19 positive primigravid patients: a comparative study - Rahman, Rushdana; Mustary, Faryal (BIRDEM Medical Journal, 2020)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a new strain of corona virus causing COVID-19. Previous studies suggested that COVID-19 is more likely to affect older males with co-morbidities. But pregnant women are at greater risk of exposure to SARS-CoV-2 infection due to physiological and immunological changes during pregnancy. This study aimed to monitor the pregnancy complications and mode of delivery. Methods: This prospective observational study was carried out in the Department of Obstetrics and Gynaecology, Dhaka Medical College Hospital, Dhaka over from May 2020 to July 2020. A total of 20 primigravid singleton pregnant women of all trimesters having COVID-19 positive reports (mild to moderate) were included in this study. Similar numbers of primigravid singleton pregnant women of all trimester having negative COVID-19 report were included in this study. Women having age between 18 and 40 years were included. Patients with multiple pregnancy, pregnancy with hypertension, heart disease, renal disease and other metabolic diseases were excluded from this study. Results: Most of the patients were between 26 and 35 years old. Mean age was 29.25 ± 4.42 years in COVID positive group and 31.10 ± 4.65 years in COVID negative group. In positive cases, most of them had gestational age below 37 weeks but in negative cases, most of them had gestational age e•37 weeks. There was significant difference in gestational age between two groups. Regarding type of delivery, in positive cases most underwent Caesarean section and in negative cases maximum were normal vaginal delivery. Regarding antenatal complication during pregnancy, abortion, premature rupture of membrane and pre term labour was found significantly higher in positive cases than that of negative cases. Respiratory distress and psychological upset were observed significantly higher in positive cases than that of negative cases. Conclusion: Regarding antenatal complications and mode of delivery, Frequency of abortion, PROM, preterm labor and LUCS was significantly higher in COVID-19 cases. Respiratory distress and psychological upset was significantly higher in COVID-19 positive cases. COVID-19 Among postnatal complications infection might increase the risk of pregnancy complications and pregnant women could have a severe clinical course of the disease. Birdem Med J 2020; 10, COVID Supplement: 71-73